2019
DOI: 10.2147/rru.s199512
|View full text |Cite
|
Sign up to set email alerts
|

<p>Expression of protease activating receptor-2 (PAR-2) is positively correlated with the recurrence of non-muscle invasive bladder cancer: an immunohistochemical analysis</p>

Abstract: Background: Matriptase, which is a Type II transmembrane serine protease, has the potential to activate several growth factors, including pro-hepatocyte growth factor (HGF). A G protein-coupled transmembrane cell-surface receptor and a protease-activated receptor 2 (PAR-2) are also required for activation by matriptase. Activation of PAR-2 has been reported to induce the progression of various cancers. In a previous study, we evaluated the correlation between upregulation of MET phosphorylation with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Pathological analysis shows that approximately 90% of bladder cancers are UC and that 5% are squamous cell carcinoma [95]. Several studies reported a positive correlation between increased expression of MET and high tumor grade, pathological staging, and survival [96][97][98][99][100]. Phosphorylation was also analyzed by immunohistochemistry [97,98].…”
Section: Significance Of Hgf-dependent Met Activation In Muscle Invasmentioning
confidence: 99%
“…Pathological analysis shows that approximately 90% of bladder cancers are UC and that 5% are squamous cell carcinoma [95]. Several studies reported a positive correlation between increased expression of MET and high tumor grade, pathological staging, and survival [96][97][98][99][100]. Phosphorylation was also analyzed by immunohistochemistry [97,98].…”
Section: Significance Of Hgf-dependent Met Activation In Muscle Invasmentioning
confidence: 99%